Physical and chemical properties of nutmeg (myristica fragrans) fruit - NEHA HALDER; K. A. ATHMASELVI (International Journal of Pharma and Bio Sciences, 2018)
This project was carried out to analyse the various physical and chemical parameters of the nutmeg fruit with an optimal purpose to feature the properties of the fruit in developing a functional food from it.The fruits procured were thoroughly cleaned and the physical properties of the whole fruit such as sphericity, aspect ratio, porosity, bulk density, coefficient of friction etc. were determined. The fruit rind was thoroughly cleaned and dried using tray dryer at a temperature of 70 for 16 hours to obtain powder which was further used for the chemical analysis. The properties such as protein content, ascorbic acid content etc. were determined. The dried fruit powder was used for the chemical analysis of the fruit. The pH value concluded that the fruit is acidic in nature giving a sour taste. The fruit was also found to have a good amount of protein, fat etc. The ash content indicated the amount of various inorganic minerals in the fruit. The physical parameters analysed puts light on the roundness of fruit for effective packaging and utilization with a way for equipment designing.